Nivel de conocimiento en la técnica grafo plásticas por estudiantes del quinto nivel de educación inicial Facultad Ciencias de la Educación y Humanidades UNAP, Iquitos 2021 - Vasquez Flores, Fiorella Atemi (2024)
The general objetive of the study Was to determine the level of knowledge of the Grapho-plastic technique presented by fifth-level students in initial education. The aspects of the methodology were determined as follows: non-experimental type of research, with a simple descriptive design, a population of 193, and a sample of 57 students. The instrument used was a questionnaire of questions applied to fifth-level students in initial education. The results show that the level of knowledge of the Grapho plastic technique in students, considering the four dimensions: Drawing, Painting, Modeling, and Tearing, indicates that they are at the achieved level with 71.9% (n=41), in the process level, 28.1% (n=16) of them. Likewise, there were no students at the initial level. It is concluded that regarding the level of knowledge of the Grapho-plastic technique in fifth-level students in initial education, considering the four dimensions, they are at the highest level, with 71.9% (n=41).